Sistem Deteksi Posisi Dan Pengambilan Bola Pada Robot Sepak Bola - Amperawan Amperawan; Destra Andika; Masayu Anisah; Marcelinus I.J (Universitas PGRI Palembang, 2022)
One of the robot contests held in Indonesia at regional and national levels is the Indonesia Sepal Bola Robot Contest (KRSBI) with wheels, which is a part of the Indonesian Robot ContestÂ which is a design and engineering competition in the field of robotics. KRSBI in 2017 is a new division organized by RISTEKDIKTI with the theme